Durable and thermally switchable polysilsesquioxane adhesives via dynamic covalent bonds: effect of a crosslinker on reversible chemistry. (24th January 2023) - Kang, Seung Hyun; Seo, Jin Young; Oh, Hyeon Ji; Lee, Jung-Hyun; Lee, Albert S.; Baek, Kyung-Youl
Abstract : Thermally switchable ladder-like poly(silsesquioxane) (LPSQ) adhesives based on Diels–Alder reaction were prepared and utilized as reversible adhesion materials. Abstract : Thermally switchable ladder-like poly(silsesquioxane) (LPSQ) adhesives using the Diels–Alder reaction were synthesized and utilized as reversible adhesion materials. The LPSQ polymer was blended with various diene crosslinkers and its reversible features were evaluated. LPSQ adhesives with long alkyl crosslinkers, including LPSQ-Oct and LPSQ-Dec, exhibit tremendous reversibility in thermally switchable adhesion. The effect of the chain flexibility of LPSQ side chains on the reversible Diels–Alder and retro Diels–Alder reactions was experimentally and theoretically demonstrated. Moreover, these thermally switchable LPSQ adhesives present excellent mechanical and thermal stabilities compared to commercial adhesives, and they are expected to be potential materials for adhesion applications.